New migrant activism: Frame alignment and future protest participation. (May 2022) - Karyotis, Georgios; Skleparis, Dimitris; Patrikios, Stratos
New migrant movements increasingly rely on unconventional forms of protest, which they strategically frame in rational terms, rather than as 'acts of desperation' that dominate public representations. This article demonstrates this empirically through a prototypical case of new migrant activism, employing discourse analysis to explore the collective framing of a hunger strike involving irregular migrants in Greece, which was, however, contested by other protest users. Drawing on rare and pertinent data collected through face-to-face interviews with hunger strikers, we find that the strategic or rationalist framing of the hunger strike, promoted by its leaders, was largely shared with individual protesters at the basis of the mobilisation, contrary to the publicly proliferated affective frames. Using quantitative methods, we show, for the first time, that the degree of frame alignment is not only important for the legitimacy of a movement but is also a significant predictor of future remobilisation in radical types of protest activity.